2003
DOI: 10.1086/375348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Comparison of Virulence Traits, Including Murine Lethality, among Different M Types of Group A Streptococci

Abstract: Epidemiological studies have proposed an association between group A streptococci (GAS) bearing a particular M serological type and pathologic conditions such as streptococcal toxic shock syndrome (STSS). M1 and M3 GAS are isolated from STSS cases more frequently, whereas M4 and M12 GAS are isolated from non-STSS cases more frequently. To investigate whether there is any difference contributing the M-type association among GAS, we compared various virulence traits, including the murine lethality of M4, M12, M1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…These observations suggest that the S. pyogenes strains (M serotypes) have evolved as distinct pathovars, harboring a specific set of chromosomally encoded fitness factors. These data fit with the epidemiological observation of an association between the M serotype and certain pathological conditions in humans and mice (158). On the other hand, a detailed analysis of DNA sequence polymorphism of the set of chromosomal virulence genes studied by Reid et al (192) revealed numerous likely horizontal transfer events between the different M strains, and the authors suspected that generalized phage transduction was responsible for at least some of these gene transfers.…”
Section: Vol 68 2004 Phages and The Evolution Of Bacterial Pathogensupporting
confidence: 78%
“…These observations suggest that the S. pyogenes strains (M serotypes) have evolved as distinct pathovars, harboring a specific set of chromosomally encoded fitness factors. These data fit with the epidemiological observation of an association between the M serotype and certain pathological conditions in humans and mice (158). On the other hand, a detailed analysis of DNA sequence polymorphism of the set of chromosomal virulence genes studied by Reid et al (192) revealed numerous likely horizontal transfer events between the different M strains, and the authors suspected that generalized phage transduction was responsible for at least some of these gene transfers.…”
Section: Vol 68 2004 Phages and The Evolution Of Bacterial Pathogensupporting
confidence: 78%
“…However, we found that GAS isolated from STSS cases produced smaller amounts of SAGs than did GAS isolated from non-STSS cases (21). Most SAGs have highly conserved secondary and tertiary structures despite minimal amino acid sequence homology.…”
mentioning
confidence: 59%
“…Individual strains were stored in brain heart infusion (BHI) broth (Difco, Franklin Lakes, NJ) containing 7% dimethyl sulfoxide at Ϫ80°C until use. They were cultured overnight in BHI broth at 37°C in a humidified 5% CO 2 incubator as described previously (21). For expression of the six-His (His 6 )-tagged proteins, Escherichia coli M15(pREP4) (QIAGEN, Tokyo, Japan) was used for transformation with expression constructs derived from pQE30 (QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations